Perlindungan Hukum Bagi Anak Korban Bullying Di Desa Tamansari Kota Bekasi - Fransiska Novita Eleanora; Ahmad (CV. Multi Kreasi Media, 2024)
Protection for children has become the responsibility of the state, and the protection provided is also the responsibility of families, teachers and the community to protect children so that they do not become victims of bullying which is increasingly widespread. Children who are victims of bullying certainly experience depression and even stress as well as feelings of fear and lack of confidence in facing the surrounding environment, and the impact also results in prolonged trauma and it is difficult to forget it, because the victim is someone who experiences suffering as a result of someone's actions or treatment other. Legal protection for children who are victims of bullying is to provide or implement their rights, such as the right to access medical services and assistance and also receive medical, as well as social and psychological services. As a result, by providing legal protection for children as victims of bullying, it can alleviate children's suffering in an effort to provide repressive protection so that children can return to experience recovery and good conditions as before in realizing true child protection.